A Transgender Gaze at Genesis 38 - Samuel Ross (University of Sheffield, 2020)
While queer interpretation of the Hebrew Bible has begun to flourish, readings which focus particularly on trans and gender-diverse experiences remain lacking. In this article, I offer a trans reading of Gen 38, the Judah and Tamar narrative, drawing the text into dialogue with a trans hermeneutic. This allows me to reflect on trans and gender-diverse experiences while also shedding new light on the biblical narrative. In the course of this reading, I focus on three narrative aspects which I believe are particularly relevant to trans and gender-diverse lives: Tamar’s precarity, her engagement in sex work, and the complexity of her motives for doing so. This reading is intended to counter transphobic uses of the Bible, contributing to a growing body of trans affirmative biblical studies and providing some new answers to questions about the text.